Revisiting the crossroads: can Oedipus take a gay turn in the 21st C?. Issue 3 (2nd July 2016) - Clarke, Jeremy
Abstract : Is our foundational story of sexual identity still relevant and valid for today, or is it wrong? Oedipus has been used in the past as a cautionary tale for the consequences of transgressive sexuality, as well as an exemplar of hetero-normative development. Perhaps most influentially he has been used recently to illustrate a mechanism that underpins the concept of a pathological organization of personality, a perverse turning of a blind eye to the truth. But is this reading mistaken? In this article I return to the crossroads with Oedipus to try to give him back – for the first time – his sexual identity. By offering a re-reading of the myth in light of how we understand the impact of internalized stigma on the formation of sexual identity today I hope to show that our psychoanalytic imagination can use the Oedipus myth to encompass a range of different developmental possibilities.